2018
DOI: 10.1002/pen.24964
|View full text |Cite
|
Sign up to set email alerts
|

UHMWPE/organoclay nanocomposites fabricated by melt intercalation under continuous elongational flow: Dispersion, thermal behaviors and mechanical properties

Abstract: The preparation of ultra-high-molecular weight polyethylene (UHMWPE)/organoclay nanocomposites by continuous elongational flow technique was investigated in a novel eccentric rotor extruder (ERE). The distribution and dispersion morphologies of organo-modified montmorillonite (OMMT) layers were revealed and observed by ash determination, wide angle X-ray diffraction and transmission electron microscopy. The thermal and thermal-mechanical behaviors were characterized by differential scanning calorimeter, therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…They found that the dispersion efficiency of the elongational flow field for nanoparticles was several times than that of the shear flow field at the same deformation rate. The elongational flow has a great effect on the dispersion and intercalation of MMT in polymer matrix, which has been demonstrated previously by many researchers 25–29 …”
Section: Introductionmentioning
confidence: 57%
“…They found that the dispersion efficiency of the elongational flow field for nanoparticles was several times than that of the shear flow field at the same deformation rate. The elongational flow has a great effect on the dispersion and intercalation of MMT in polymer matrix, which has been demonstrated previously by many researchers 25–29 …”
Section: Introductionmentioning
confidence: 57%
“…Therefore, the researchers have demonstrated that a polymer nanocomposite produced by melt processing under an elongational flow field exhibits superior mechanical properties because of not only superior dispersion qualities of the nanoparticles but also lower degradation of shear-sensitive polymers. Researchers have reported the superior efficacy of elongational flow field in the mixing of other nanofillers, such as nanoclay and carbon nanotubes, , in various polymers.…”
Section: Role Of Rheology In the Development Of The Morphologies Of P...mentioning
confidence: 99%
“…Polymer/filler composites prepared by ERE based on elongational flow have attracted the attention of many researchers. [20][21][22] It has been reported that the elongational flow has many advantages in polymer processing, including a short thermo-mechanical history, wide adaptability, and outstanding miscibility. [23][24][25][26][27] 2.3 | Sample preparation…”
Section: Experimental Devicementioning
confidence: 99%